Hubungan Usia Primigravida dengan Kejadian Preeklampsia Berat di RSUD Dr. Moewardi - Amalia, Fatkhurrohmah Leo; Wiryanto, Tri Budi; Hanim, Diffah (Nexus Kedokteran Klinik, 2012)
Background: Age factor holds crucial cause of health level and the wealth of pregnant mother and the baby. In young age, the development of reproduction organs and the physiological function is not optimal yet, also the emotional and psychological phase of the mother is not mature enough. Therefore in pregnancy, the mother is not yet able to respond her pregnancy completely and also there often occurs complication. Three pregnancy complications that become the main cause of motherâs death in obstetric section are bleeding, infection, and pregnancy hypertension (preeclampsia). Preeclampsia is a disorder of multi organ that is very distinct in pregnancy, which is noted as occurrence of hypertension and proteinuria in pregnancy age above 20 weeks. This research purpose for analyzing the relation between the age of primigravida with the occurrence of severe preeclampsia in RSUD Dr. Moewardi. Methods: This research is observational analytic with cross-sectional. Research is done in April-June 2012 in RSUD Dr. Moewardi section Obstetrics and Gynecology. The taking of sample is done with the way of purposive sampling. This research got 60 samples consisted of 30 samples age < 20 years old and 30 samples age 20-35 years old with the diagnosis of severe preeclampsia 42 samples. The data which is got then analyzed with the use of statistic test Spearman. Results: The risk factors of severe preeklampsia in RSUD Dr. Moewardi are the age and the graduation of primigravida. The statistic test shows there is a significant relation between the age of primigravida with the occurrence severe preeclampsia (p â¤ 0.05) Conclusions: There was a significant relation between the age of primigravida with the occurrence severe preeclampsia (p Â= 0.024) whereas the strength of the positive correlation is weak (r = 0.291) Keywords: primigravidaâs age, severe preeclampsia.Â